PEMBERDAYAAN PEREMPUAN (Transformasi menuju partisipasi politik) - Marniyati, Sabar (Responsibilitas, 2011)
The  capacity  of women  in  politics  in  Indonesia  to  date  has not  shown  significant  progress.  This  is  evident  from  not   fulfilling the  quota  of  women  serving  in  government  and   political institutions,  thus  triggering   the  apolitical  attitude of women. Therefore,  empowerment  of  women  in  politics  into a critical discourse  to  encourage more  women  go  into   politics. Efforts must be  made  by  government  and  non  government agencies that have the empowerment of women equal to men.